THE REFLECTION OF SOCIAL ACTIVITIES AND MARRIAGE LIFE OF BRITISH SOCIETY IN 19TH CENTURY AS SEEN IN EMMA BY JANE AUSTEN - Robby Satria (Universitas Putera Batam, 2017)
This research discusses the application of Sociology of Literature theory proposed by Allan Swingwood which proposed that literary work is a social document which has the reflection of the situation of people in society at the certain time. In this research the writer analyses the novel Emma written by Jane Austen published in 1816. Here, the writer analyses the social activity and marriage life in society. This research is qualitative research by using descriptive method. Data is gained by library research method and other sources taken from web. In this research, the data is analysed based on its relationship with the purpose of the research both instrinsic and extrinsic element in literary work. After comparing the social history of the real condition of British society in 19th century with the plot story in novel “Emma’ by Jane Austen, the writer found that visiting and ball are the social activities which are commonly done by British society in 19th century. The writer also concludes that social class has a close relationship with marriage where it can increase someone’s social status in society.